The Influence Of Live Streaming And Flash Sale On Impulse Buying Among Shopee App Users In Bengkulu City - Dewi, Fitria; Soleh, Ahmad; Febliansyah, Rahman (Universitas Dehasen Bengkulu, 2024)
Marketers and retailers employ strategies to attract consumer attention and influence their purchasing decisions. Two increasingly popular strategies are flash sales and live streaming which utilize technology advancements to create a more engaging and dynamic shopping experience. The research aims to determine the influence of live streaming and flash sales on impulse buying among Shopee app users in Bengkulu city. The sample in this study consists of 100 respondents who use the Shopee app in Bengkulu. Data collection method involves the use of questionnaires. The analysis method employs the SmartPLS analysis tool version 4.0. The research results indicate that live streaming has a significant and positive influence on impulse buying among Shopee app users in Bengkulu, as the t-statistic value is 4.082 > 1.96 and the p-value is 0.000 < 0.05. The original sample value shows a positive value of 0.333, indicating that the relationship between the live streaming variable and impulse buying is positive. This means that the better the live streaming, the higher the impulse buying. Flash sales also have a significant and positive influence on impulse buying among Shopee app users in Bengkulu, with a t-statistic value of 7.045 > 1.96 and a p-value of 0.000 < 0.05. The original sample value shows a positive value of 0.517, indicating that the relationship between the flash sale variable and impulse buying is positive. This implies that the higher the flash sale provided by the seller, the higher the impulse buying.